2016
DOI: 10.1038/srep31222
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor alternative splicing is regulated by insulin signaling and modulates beta cell survival

Abstract: Type 2 Diabetes (T2DM) affects more than 300 million people worldwide. One of the hallmarks of T2DM is peripheral insulin resistance, in part due to unproductive insulin signaling through the insulin receptor. The insulin receptor (INSR) exists as two isoforms, INSR-A and INSR-B, which results from skipping or inclusion of exon 11 respectively. What determines the relative abundance of the different insulin receptor splice variants is unknown. Moreover, it is not yet clear what the physiological roles of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 45 publications
2
68
0
1
Order By: Relevance
“…The manipulated expression of SRSF1 is frequently observed during the organogenesis and carcinogenesis [115]. More than 500 potential candidates, including insulin receptor ( INSR ) were identified as the potential candidates of SRSF1 by using the RNA-seq approach [116]. INSR gene was demonstrated to generate two alternatively-spliced variants in a spatial-temporal manner [116].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
See 3 more Smart Citations
“…The manipulated expression of SRSF1 is frequently observed during the organogenesis and carcinogenesis [115]. More than 500 potential candidates, including insulin receptor ( INSR ) were identified as the potential candidates of SRSF1 by using the RNA-seq approach [116]. INSR gene was demonstrated to generate two alternatively-spliced variants in a spatial-temporal manner [116].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…More than 500 potential candidates, including insulin receptor ( INSR ) were identified as the potential candidates of SRSF1 by using the RNA-seq approach [116]. INSR gene was demonstrated to generate two alternatively-spliced variants in a spatial-temporal manner [116]. The exon 11-excluded INSR ( INSR-A ) transcripts were predominantly expressed in embryonic and cancerous cells [116], whereas the exon 11-included INSR ( INSR-B ) transcripts were widely noted in the pancreatic β-cells, skeletal muscle, and adipocytes [117].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…IR-B is associated with stronger insulin binding, while isoform IR-A binds both insulin and IGF20. Studies found IR-A often aberrantly expressed in tumour cells, thus increasing its responsiveness to insulin and IGF and explaining the cancer-promoting effect of hyperinsulinaemia observed in type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%